Design Stealth Fast Attack Vehicle (SFAV) 18 Meters Using Numerical Method as Coastal Patrol Vessels - Kusuma, Cahya; Kusdiana, Wawan; Syaifi, Muhammad; Sumarsono, Wika Adhietama (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2023)
The design of the 18 Meter Stealth Fast Attack Vehicle (SFAV) with Maxsurf software and the Savitsky method as a coastal patrol vessel is a fast ship that has stealth capabilities that can be used as a coastal patrol vessel area 12 NM to supervise fishing vessels so that fishing and marine resources do not damage the environment such as the use of tiger trawls and marine bombs. The ship model resistance and stability are analyzed using the numerical software Maxsurf Modeller Advanced V8i. Lines plan and general arrangement using AutoCAD software. Model analysis, the design of the SFAV Interceptor Vehicle uses the spiral design method, while the prediction of the resistance value uses the Savitsky preplanning and planning methods. Ship stability uses standardized values issued by IMO, which can be applied to the Maxsurf Stability Advanced V8i software. The analysis results of resistance prediction software and numerical successively 43.416 kN, 45.526 kN, with a difference of 4.6%. The stability analysis is predicted using heel angle model analysis on Maxsurf stability software in various conditions. The results meet IMO standards and capable of sea stage 4. The existence of SFAV ships will help security patrols to protect the coastal area.